Numerical Simulation of Heat Transfer in Channel with a Longitudinal Pressure Gradient - Tsynaeva A.A. (Problems of the Regional Energetics)
The work is devoted to the study of heat transfer in channels with a longitudinal pressure gradient. The aim of the work is to develop methods for increasing the heat transfer intensity in channels with a longitudinal pressure gradient. The goal was achieved by developing the original design of the surface intensifier, made in the form of a horseshoe-shaped dimples, as well as by conducting heat transfer studies in the channel with a longitudinal pressure gradient and dimples of various geometries and locations. It was found that a numerical solution using the k-epsilon turbulence model shows not sufficiently stable results, including the values of local heat transfer coefficients can exceed 2 ... 2.5 times their actual values for a single dimple. Moreover, the use of the k-w-sst turbulence model shows more stable results. The most significant results obtained in the work are as follows: it was revealed that the use of holes, their geometry and location have a significant effect on the heat transfer intensity in a channel with a longitudinal pressure gradient; the design of the original horseshoe-shaped dimples has been developed, the use of which allows to intensify heat transfer by 13 ... 47% depending on the Reynolds number when they are arranged in three rows in the corridor order compared to staggered hemispherical dimples; when comparing the efficiency of using the developed dimples with hemispherical holes installed in three rows in the corridor order, the heat transfer increased by 21 ... 51% when the Reynolds number changed from 3000 to 15000.